Autonomous delivery robot - Zavin, Sarin Rahman; Rahaman, Kazi Habibur; Nayeem, Safat Ahmed; Bin Mujahid, SK Rubayet; Sarkar, Swapnil (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.